Design of a Microstrip Antenna Structure for WBAN Devices at 2.45 GHz (ISM) Band - Gupta, Vipin; ., Anupma; Narayan Mohanty, Mihir (International Journal of Engineering and Technology, 2018)
In this paper, a microstrip antenna is presented for wearable devices operating at unlicensed Industrial, Scientific and Medical (ISM) band. Antenna is designed on 34 Ã— 28 mm2 sheet of low loss Rogers 5880 material. An equivalent biological tissue model is designed for the simulation. A wide bandwidth of 400 MHz can easily withstand the detuning effect caused by body posture and movement. Effect of electromagnetic radiation on human tissue is also analyzed for safety.Â  High gain, low SAR makes antenna a good candidate for wearable devices.Â